1996
DOI: 10.1897/1551-5028(1996)015<1584:eopahb>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCB and Hexachlorobenzene Biota–sediment Accumulation Factors Based on Ingested Sediment in a Deposit-Feeding Clam

Abstract: Abstract-Contaminated sediment exposure experiments were conducted using a marine deposit-feeding clam (Macoma nasuta) to determine biota-sediment accumulation factors (BSAFs) based on ingested sediment and fecal organic carbon. Internal, or gut, BSAFs were determined for hexachlorobenzene and 13 polychlorinated biphenyl congeners and were compared to those found with the standard method of calculating BSAFs, which uses the organic carbon and contaminant concentration of the whole or external sediment. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…An additional study by Drouillard et al (2008) For N. virens, the 28-d and steady-state BSAFs were similar among congeners and between the Arthur Kill and Newark Bay sediment exposures ( Figure 16). The BSAFs obtained in this study were lower overall compared to previously reported values (0.19-1.41) (Pruell et al 1993 Ferraro et al 1990Ferraro et al , 1991Brannon et al 1993;Pruell et al 1993;Boese et al 1995Boese et al , 1996. Overall, the BSAFs obtained in this study for M. nasuta were lower compared to previously reported values.…”
Section: Polychlorinated Biphenyls (Pcbs)contrasting
confidence: 86%
See 1 more Smart Citation
“…An additional study by Drouillard et al (2008) For N. virens, the 28-d and steady-state BSAFs were similar among congeners and between the Arthur Kill and Newark Bay sediment exposures ( Figure 16). The BSAFs obtained in this study were lower overall compared to previously reported values (0.19-1.41) (Pruell et al 1993 Ferraro et al 1990Ferraro et al , 1991Brannon et al 1993;Pruell et al 1993;Boese et al 1995Boese et al , 1996. Overall, the BSAFs obtained in this study for M. nasuta were lower compared to previously reported values.…”
Section: Polychlorinated Biphenyls (Pcbs)contrasting
confidence: 86%
“…For 2,3,7,8-TCDD, a factor of four has been suggested to adjust 28-d N. virens tissue residues to the steady-state concentration used in risk estimations while a factor of one (i.e., no correction) is used for the clam M. nasuta based on data from Pruell et al (1990). More recent work (e.g., Boese et al 1995Boese et al , 1996Boese et al , 1997 reports a longer time period required for M. nasuta to reach steady state, implying that a correction factor greater than 1 is warranted. This report presents evidence that these correction factors are not necessarily applicable.…”
Section: Executive Summarymentioning
confidence: 99%
“…This finding suggests that A. granosa is a potential indicator for pollution in a marine environment. In a previous study, it was found that molluscs have the potential to be used as bio-indicators for the contamination of Cd and Zn in water and sediment of an estuarine environment 14 and it was proposed as a simple model for predicting the bioaccumulation of sediment-associated natural organic contaminants by in faunal invertebrates [59][60][61] . Heavy metal BSAF in Perna viridis reflects the degree of industrialization and population density in coastal areas of Hong Kong 62 .…”
Section: Resultsmentioning
confidence: 99%
“…This may occur because the uptake clearance from water is greater than for sediment Landrum 1989. Contaminant concentrations in filter feeders and deposit-feeders are unaffected by digestive processes or passage through the gut Boese et al 1996.…”
Section: Organism Toxicokineticsmentioning
confidence: 99%